Topic management in French L2. A longitudinal conversation analytic study - Koenig, Clelia (My University, 2013)
Drawing on Conversation Analysis, this paper investigates free occurring conversational data in French as a second language. Its focus of attention is a debated concept within the conversation analytic approach: topic management. After an overview of the existing literature on topic management and the conceptualisation of learning and L2 interactional competence, the main part of the article will be concerned with data analysis. The data show an au-pair girl speaking French with her host-family at different points in time. The longitudinal design allows describing in detail and conceptualising L2 interactional competence and its development. In fact, taking into consideration interactional aspects, such as sequential and action organisation, contributes to a better understanding of L2 learning. The results show how topic management is not only the object of, but also the means for, learning an L2, whilst being socialised into the very same L2. This article contributes to an ongoing debate in the field of CA and, especially, CA-SLA about conceptualising L2 learning and tracking the development of L2 interactional competence.
Keywords: topic management; second language acquisition; conversation analysis; longitudinal study